AlN films deposited by dc magnetron sputtering and high power impulse magnetron sputtering for SAW applications. (18th March 2015) - Aissa, K Ait; Achour, A; Elmazria, O; Simon, Q; Elhosni, M; Boulet, P; Robert, S; Djouadi, M A
Abstract: In this work, aluminium nitride (AlN) films were deposited on silicon substrates buffered by an epitaxial AlN thin film for surface acoustic wave (SAW) applications. The films were deposited by dc magnetron sputtering (dcMS) and high power impulse magnetron sputtering (HiPIMS) deposition techniques. The structural properties of AlN films were investigated using x-ray diffraction (XRD), Raman spectroscopy, scanning electron microscopy and atomic force microscopy. In both cases of films deposited by dcMS and HiPIMS, the XRD results showed that the obtained films are oriented, with full width at half maximum rocking curves of around 1°. Raman spectroscopy revealed higher residual stress relaxation in the AlN epilayers grown by HiPIMS compared to AlN grown by dcMS, highlighted by a blue shift in the E2(high) Raman mode. The SAW measurements indicated an insertion loss of AlN-SAW devices of about 53 and 35 dB for the AlN films deposited by dcMS and HiPIMS respectively. The relation between the structural properties of AlN and the characteristics of AlN-SAW devices were correlated and discussed.